Using Online Platform for Community Engagement During the Covid-19 Pandemic - Chawa, Anif (UIN Sunan Ampel Surabaya, 2021)
The spread of the Coronavirus disease across the world remains unstoppable with destructive negative impacts on health and the socio-economic life of communities. Government, organizations and impacted communities have established various development programs to overcome these impacts. However, multiple protocols in combating the virus (wearing mask, social distancing or staying 6 feet apart and avoiding crowds) have hampered the distribution of these programs to the communities. This study aims to examine how community engagement process has been conducted by using online platform. The study sourced data from fifteen community development programs conducted by undergraduate students. Before the pandemic, these programs were distributed to the communities offline. This study found several online platforms which were used mostly by those students including webinar and meeting software, such as zoom, website and social media like Instagram and Facebook. These platforms were employed to conduct webinar, inform, and involve other groups or communities in the programs. As a result, the communities have become more active and familiar in utilizing online platforms to establish various development programs. However, this study also identifies some problems which hinder the community engagement process including online communication issues and lack of the accessibility of communities using the internet.